2020
DOI: 10.1017/jfm.2020.424
|View full text |Cite
|
Sign up to set email alerts
|

Crest speeds of unsteady surface water waves

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 81 publications
(157 reference statements)
3
21
0
Order By: Relevance
“…Derakhti et al. 2020; Fedele, Banner & Barthelemy 2020) does lead to a level of uncertainty in the resultant time-series. This is managed by filtering the data with a running mean of width , which we find effectively removes high-frequency noise without significantly smoothing the temporal variability in the data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Derakhti et al. 2020; Fedele, Banner & Barthelemy 2020) does lead to a level of uncertainty in the resultant time-series. This is managed by filtering the data with a running mean of width , which we find effectively removes high-frequency noise without significantly smoothing the temporal variability in the data.…”
Section: Methodsmentioning
confidence: 99%
“…Cubic interpolation is used to determine the location of x + and the value of the energetic quantities at this point, but the unsteady movement of the crest (e.g. Derakhti et al 2020;Fedele, Banner & Barthelemy 2020) does lead to a level of uncertainty in the resultant time-series. This is managed by filtering the data with a running mean of width 0.15T p , which we find effectively removes high-frequency noise without significantly smoothing the temporal variability in the data.…”
Section: The Crest Ensemblementioning
confidence: 99%
“…Studies such as these have identified the main controlling parameters of breaking waves, namely the breaking speed and the wave slope at breaking S = ak, where a is the wave amplitude, and k is the wavenumber. The bandwidth of the wave packet is also important, and the detailed kinematics before breaking, in particular a significant slowdown of the wave crest, have been discussed in order to propose breaking threshold criteria (Banner et al 2014;Saket et al 2017;Derakhti et al 2020;Fedele et al 2020), although we will neglect its influence from here onwards.…”
Section: Laboratory Experiments and Direct Numerical Simulations Of C...mentioning
confidence: 99%
“…As wave energy focuses through linear or nonlinear processes, local conditions on a wave surface become unstable and cause breaking, which transfers energy and momentum to the water column. The geometry and kinematics of the breaking waves have been studied extensively (Longuet-Higgins & Cokelet 1976;Perlin, Choi & Tian 2013;Schwendeman & Thomson 2017;Fedele, Banner & Barthelemy 2020), and the identification of a breaking threshold with approaches based on the wave kinematics, dynamics or geometry remains a longstanding issue (Melville 1982;Banner & Peirson 2007;Perlin et al 2013), with recent work discussing the link between the breaker kinematics and dynamics (Saket et al 2017;Derakhti et al 2020;Pizzo 2020).…”
Section: The Broader Contextmentioning
confidence: 99%
“…Nevertheless, Stansell & MacFarlane (2002) questioned the physical significance of phase reversal effect emphasised by Melville (1983) (reduction of the local phase speed below zero), as it can be subject to the peculiarity of Hilbert transform. On the other hand, Banner et al (2014), Fedele, Chandre & Farazmand (2016 and Fedele, Banner & Barthelemy (2020) showed that the crest speed of a nearly breaking wave can significantly deviate from the phase speed suggested by both (2.13) and (4.16). The actual wave crest speed exhibits very fast variations: whether a crest experiences slowing down or speeding up depends on the dispersion regime it belongs to.…”
Section: Dispersion Variationmentioning
confidence: 88%